UNDERSTANDING THE INSTRUMENTS OF POWER EFFECTS ON THE MILITARY INSTRUMENT OF POWER IN MULTI-DOMAIN OPERATIONS: A CASE STUDY FOR HUMAN INTELLIGENCE FROM A TRAINING PERSPECTIVE - Kis, Alexandru; Marza , Andrei (International Journal of Legal and Social Order, 2025)
This paper investigates the effects of the diplomatic, informational, and economic instruments of power (IoPs) on the military IoP within Multi-Domain Operations (MDO), focusing on human intelligence (HUMINT) as a case study from a training perspective. It argues that HUMINT professionals must be trained not only in classical collection and influence skills but also in the ability to understand, navigate, and synchronize with other IoPs in a multi-domain environment. To this end, the study evaluates the conceptual foundations of IoPs in MDO, examines their interplay across the continuum of conflict, assesses the role of HUMINT in this context, and outlines training needs and approaches for HUMINT professionals. Ultimately, it seeks to contribute to the development of effective, future-proof training programs that enable NATO and partner personnel to operate effectively in the complex reality of modern conflict.